Time–frequency analysis of the sea state with the Andrea freak wave - Z. Cherneva; C. Guedes Soares (Natural Hazards and Earth System Sciences, 2014)
The nonlinear and nonstationary properties of a special field wave record are analysed with the Wigner spectrum with the Choi–Williams kernel. The wave time series, which was recorded at the Ekofisk complex in the central North Sea at 00:40 UTC (universal time coordinated) on 9 November 2007, contains an abnormally high wave known as the "Andrea" wave. The ability of the Wigner spectrum to reveal the wave energy distribution in frequency and time is demonstrated. The results are compared with previous investigations for different sea states and also the state with Draupner's abnormal "New Year" wave.